Optimalisasi Pembelajaran Tajwid di TPQ Desa Ngusikan Jombang: Pendampingan Keagamaan dan Tantangan Pendidikan di Era Digital - Anandita, Septian Ragil; Hayati, Irma Nur; Wafa, M. Aliyul; Waqfin, Mohammad Saat Ibnu; Hilmi, Samudra; Ghoffar, Abdul; Zahroh, Atania; Izzatilla, Izzatilla; Muniroh, Igfirotum; Aziz, M. Thoriqul (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This community service program focuses on optimizing tajwid learning for children at TPQ (Qur'anic Learning Centers) in Ngusikan Village, Jombang, and providing religious guidance to parents. Through a practical approach to teaching tajwid, children are expected to improve their Qur'anic reading accuracy. In parallel, a series of religious discussions were held to assist parents in addressing educational challenges associated with the digital age. The program showed a significant improvement in children's understanding of tajwid, as well as a high level of enthusiasm among parents who participated in the parenting discussions. The outputs of this program include a practical Tajwid guidebook for students and teachers, as well as a parenting guidebook designed to help parents navigate Islamic parenting principles in the digital era.